Penerapan Model Pembelajaran Berbasis Stem (Science, Technology, Engineering And Mathematic) Untuk Meningkatkan Kemampuan Pemahaman Konsep Peserta Didik Pada Pokok Bahasan Pengukuran Dikelas X SMA N 10 Tidore Kepulauan - Juliyanti M. Liko (KUANTUM: Jurnal Pembelajaran dan Sains Fisika, 2023)
This research is a classroom action research that aims to find out whether the STEM-based learning model can improve the conceptual understanding of class X students of SMP Negeri 10 Tidore Kepulauan. The research method used was qualitative and the subjects of this research were class X students of SMP Negeri 10 Tidore Kepulauan in the odd semester of 2023 with a total of 28 students. Sources of data from teachers and students. Research data collection techniques were carried out using observation sheets carried out by learning models and test questions. The data obtained were analyzed by descriptive qualitative. The results showed that the average score of students in cycle I was 60. Meanwhile, in cycle II, the average score of students was 82. This shows an increase in students' understanding of concepts. From the results of this study it can be concluded that applying the STEM-based learning model to class X students of SMA Negeri 10 Tidore Kepulauan can increase.